Audición y conocimiento :Influjo del estilo perceptivo a través del oído en la elaboración del conocimiento y su aplicación en el ámbito educativo - Vilatuña Correa, Fausto Danilo (2015)
This research is an analysis about how philosophy, neuroscience and pedagogy, have as common theme the study of brain, mind, and education, and answer the current need to develop educational practice with neuroscientific bases, it is classified in the field of educational neuroscience. When these disciplines work together, generate a transdisciplinary knowledge, which enables the education community think philosophically in the ability to perceive the world through sensory systems, and how they co-evolve with learning systems and human action, thus achieving unite scientific knowledge and educational practice. The philosophy of sounds and auditory perception is an emerging area in the field of philosophy of perception, which goes beyond the visual understanding of the nature, objects, content, and varieties of perception. On this basis the contribution of auditory perceptual style, that is, establishing the construction of sound sense from the specialized use of hearing according to structure a linguistic discourse in its real-emotional, clear sound context own you will see in the process of teaching and learning. Therefore, starting from the cerebral substrate underlying auditory perception and establishing the foundations of knowledge, educational implications are proposed based on an auditory aesthetic that enhances the analytical reading and music appreciation.